(untitled) (Jurnal Bahasa, 2001)
This article tries to elaborate and prove that a meaningful poem must be in the form of a strong poetic discourse. The strength of a poetic discourse is viewed from the application of the theory of linguistic formation and analysis that is adapted to the poem. The application of the discourse theory is viewed from the satisfaction of such criteria as the continuence, exclusion and replacement of elements in the text that cohesively comprise the meaning or unified and tied meaning and maintaining the coherence in the unified form in the poem. A cohesion is a strategy that proves the coherence that forms what is known as the "message" in the poem. In addition, the formation of message is also viewed from the formation of meaning that unites the diction based on the collocational measurement. Evidently the poem by A. Aziz Deraman are composed as a strong discourse based on that measurement. The strength of a poetic discourse is also viewed from the role of several textual connectors in a meaningful text. All of them are looked into in order to prove the formation of strong messages hidden in the diction and relates their formation by using the relationship between new and old informations tied in the poem, that their unified messages are attained coherently through the semiotic interpretation of the text, that are present in Kau dan Aku, a collection of poem by A. Aziz Deraman.